Sleep, mood, and depression - Toh, Rachel (2016)
Emerging evidence suggests a close and bidirectional effect between sleep and mood and sleep and depression. Evidence converge in different populations to support the idea that poor sleep leads to worse mood and consequently, low mood leads to poor sleep. Sleep disturbances were found to predict the onset of depression and vice versa. Interestingly, although sleep deprivation usually produces undesirable effects, it has been found to be a potential treatment for depressed individuals. This review aims to (a) provide a synthesis of research investigating sleep and mood; and sleep and depression (b) propose a cognitive model that supports the relationship; and (c) summarize the efficacy of sleep deprivation as a treatment for mood disorders.